2023
DOI: 10.1021/acsomega.3c01247
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure Revision, and Anti-inflammatory Activity Investigation of Putative Blumeatin

Abstract: Blumeatin, reported herein, bearing two hydroxyl groups at C3′ and C5′ of ring B, is isolated from the traditional Chinese medicine Blumea balsamifera. But the isolation procedure of blumeatin from plants has limitations of prolonged duration and high cost. A procedure featuring Lewis acid-catalyzed ring closure and chiral resolution via Schiff base intermediates is provided here to prepare optically pure blumeatin and its R-isomer efficiently. Furthermore, the structure revision of putative blumeatin based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Another recent publication by Xia et al in 2023 stated that blumeatin was synthesized and confirmed its hydroxyl groups at positions C-3′ and C-5′ by experimental NMR spectroscopy, and they only reported selected IR peaks rather than detailed individual vibrational modes as we present here. They also mentioned that the isolation procedure of this flavonoid from plants has limitations of prolonged duration and high cost …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent publication by Xia et al in 2023 stated that blumeatin was synthesized and confirmed its hydroxyl groups at positions C-3′ and C-5′ by experimental NMR spectroscopy, and they only reported selected IR peaks rather than detailed individual vibrational modes as we present here. They also mentioned that the isolation procedure of this flavonoid from plants has limitations of prolonged duration and high cost …”
Section: Resultsmentioning
confidence: 99%
“…They also mentioned that the isolation procedure of this flavonoid from plants has limitations of prolonged duration and high cost. 106 …”
Section: Resultsmentioning
confidence: 99%
“…In vivo experiments on rodents demonstrated that blumeatin, isolated from B. balsamifera, protected liver against pathological changes induced by the carbon tetrachloride or thioacetamide intoxication [285]. Anti-inflammatory activity of the compound was confirmed in vivo by ear-swelling experiments on mice [279]. (+)-Dihydroquercetin (taxifolin) isolated from flowers of I. japonica demonstrated inhibitory activity against topoisomerase I (IC50 = 55.7 μM) and II (IC50 = 3.0 μM) [242].…”
Section: Biological Activity Of Flavanones and Flavanonolsmentioning
confidence: 99%
“…In some cases sterubin was erroneously identified as blumeatin. The structure of the "putative blumeatin" was corrected by Xia et al 2023[279];2 Published as a metabolite of Inula cappa, corrected in 1984 by Goswami et al[280].…”
mentioning
confidence: 99%
“…[ 6‐9 ] However, the HPLC method based on Cellulose tris(3,5‐dimethylphenyl carbamate) CSPs are not available to separate the single enantiomers of 5,7,2'‐trihydroxyflavanone (2'OH‐TFVN) efficiently whereas 4'‐OH‐TFVN was easily separable into its two enantiomers. [ 10,11 ]…”
Section: Introductionmentioning
confidence: 99%